2018
DOI: 10.2172/1459118
|View full text |Cite
|
Sign up to set email alerts
|

Design Studies for Deep-Water Floating Offshore Vertical Axis Wind Turbines

Abstract: Deep-water offshore sites are an untapped opportunity to bring large-scale offshore wind energy to coastal population centers. The primary challenge has been the projected high costs for floating offshore wind systems. This work presents a comprehensive investigation of a new opportunity for deep-water offshore wind using large-scale vertical axis wind turbines. Owing to inherent features of this technology, there is a potential transformational opportunity to address the major cost drivers for floating wind u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The optimal VAWT blade architecture was analyzed during the previous design studies performed by Sandia, identified as the system with the most potential to reduce blade cost for the same blade radius and rotor swept area [1]. The design studies analyzed two primary design types, the classic Darrieus VAWT along with V-VAWT designs.…”
Section: Chapter Rotor Selection and Cost Analysis 21 Rotor Definitimentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal VAWT blade architecture was analyzed during the previous design studies performed by Sandia, identified as the system with the most potential to reduce blade cost for the same blade radius and rotor swept area [1]. The design studies analyzed two primary design types, the classic Darrieus VAWT along with V-VAWT designs.…”
Section: Chapter Rotor Selection and Cost Analysis 21 Rotor Definitimentioning
confidence: 99%
“…The design and cost estimation for the platform, mooring, and installation represent a significant body of work performed as part of this study, with greater detail provided in Section 5 and Reference [2]. The VAWT rotor design study and optimization utilized in this study were based on findings from previous work summarized in Section 2 and Reference [1]. The remaining cost components are established within this report from literature review and using models developed by the National Renewable Energy Laboratory.…”
Section: Chapter 8 Levelized Cost Of Energy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As wind energy costs have come down, the opportunity to fill this need by advancing the potential of wind turbine technology is at an all-time high as a part of the initiative to reduce greenhouse gas emissions and provide greater generation by renewable sources. The wind energy community has been mostly focused on Horizontal Axis Wind Turbines (HAWTs), but recently another type of turbine named Vertical Axis Wind Turbines (VAWTs) (Bhutta et al (2012); Sutherland et al (2012)) have garnered interest especially in offshore locations (Griffith et al (2018); Möllerström et al (2016)). VAWTs have some distinct advantages over HAWTs because of their low center of gravity (c.g), absence of pitch and yaw mechanism, directional independence to wind and low sound emission (due to low operational TSR) (Griffith et al (2018); Möllerström et al (2016)).…”
Section: Introductionmentioning
confidence: 99%
“…2a). Several different rotor types [64] and floating system configurations [25] have been evaluated for a floating VAWT system [29,30]. Meanwhile, research on VAWTs is conducted on a global scale at universities, and some issues do not have a definite answer.…”
Section: Introductionmentioning
confidence: 99%